PROCESO DE CONTRATACIÓN DE PERSONAL EN EL GAD DE URDANETA - BOHORQUEZ ZAMBRANO, ANDY FRANCISCO (2018)
The present theme is very common in different public institutions, which are defined as the process of hiring personnel in the Autonomous Decentralized Government of the Urdaneta Canton. The situation that arises not only in administrative areas, this has a significant influence, it is a very important aspect that should be highlighted and that affects the economic level commonly to institutions of the Ecuadorian state